EFEKTIVITAS PENAMBAHAN PAC SEBAGAI PENGOLAHAN AWAL DENGAN FLOTASI UNTUK MENURUNKAN FOG, BOD SERTA TSS MENGGUNAKAN KOMBINASI KOAGULASI PADA LIMBAH KAWASAN INDUSTRI NGORO PERSADA - Haryo Bimo Herlambang; Euis Nurul Hidayah (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
Many techniques have been developed in wastewater treatment process which features a unit that can remove particles or flocs that tend to be difficult to settle, in which using a settling unit is less effective. This research aims to determine the reduction and the effectiveness of flotation units on the fat oil content, TSS, and BOD in the presence of the influence of PAC coagulants and recirculation. The result of this research shows that the best reduction in fat oil, TSS, and BOD content is at a recirculation ratio of 100% with the addition of a coagulant of 15ppm in which the percentage of reduction in fat oil is 75.00%, the percentage reduction in TSS is 81.48%, and the percentage reduction in BOD is 85.33%.